Perancangan Sistem Informasi Pengolahan Data Akademik Pada Pendidikan Anak Usia Dini Berbasis Website - Fikastiana Cahya; Theresia Wati; Erly Krisnanik (Journal of Applied Computer Science and Technology)
The use of information technology, especially in education, is very important today, because almost all educational institutions use technology to support the performance of employees and teachers. Academic data processing in educational institutions, especially in early childhood education needs to be considered because currently in implementing student data processing is still done manually. Manual data collection is considered quite slow because it requires very high accuracy to reduce the occurrence of errors, duplication of data, and to maintain the accuracy of the data. Data recording and reports on ledgers often experience loss because each year the data continues to increase and it is difficult to find and require long student data. The solution to the problems that occur in early childhood education is to build a website-based academic data processing information system that can adjust to needs and overcome problems that occur. So, the purpose of this study is to design a website-based academic data processing information system to facilitate PAUD in processing student academic data. In developing this system using the prototype method and the programming language PHP. The results of the study show that the use of the prototype method is very helpful in the design process where it functions in the relationship between the user and the designer in order to know what is needed so that the application built will be appropriate and can function as a medium of information and communication to parents of students with schools and to help PAUD processing student data